Perlindungan hukum terhadap anak korban pemerkosaan oleh Tenaga Pendidik ditinjau dari perspektif Victimologi - Nabila Nurailida; Hana Faridah S.H.,M.H (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Sexual violence against children is a form of human rights violation that has serious impacts on the physical, psychological, and social conditions of victims. Cases of rape against children perpetrated by educators in Islamic boarding schools demonstrate structural vulnerabilities influenced by power relations between educators and students and a culture of strong obedience to authority. This study aims to analyze legal protection for child victims of rape perpetrated by educators in Islamic boarding schools and examine recovery efforts for victims from a victimology perspective. This study uses a normative juridical research method with a statutory regulatory approach and a conceptual approach, analyzed through primary, secondary, and tertiary legal materials. The results show that normative legal protection for child victims of sexual violence has been regulated in various laws and regulations, such as the Child Protection Law and the Law on Sexual Violence Crimes. However, in practice, law enforcement still faces obstacles in the form of power relations, social stigma against victims, and a criminal justice system that is still oriented towards the perpetrator. From a victimology perspective, protection and recovery for victims must be carried out comprehensively through a victim-oriented approach, which includes psychological, social, economic, and legal recovery. Therefore, synergy between law enforcement officials, child protection agencies, educational institutions, and the community is needed to ensure that victims' rights are optimally fulfilled.